PERUBAHAN FORCE NIKEL TITANIUM CLOSED COIL SPRING DAN ELASTIC CHAIN TERHADAP PERUBAHAN TEMPERATUR - Zulfan Muttaqin; Rekka Rekka; Riris Aprila Pasaribu; Chandra Susanto (Universitas Baiturrahmah, 2020)
Introduction: Fixed orthodontic appliances which made of nickel titanium closed coil spring dan elastic chain is the most commonly used in dentistry. There are various factors that able to change the force of orthodontic appliances such as temperature, pH, and time. The purpose of this research is to find out the influence of temperature toward the force changes in nickel titanium closed coil spring and elastic chain. Method: The method that used in this study was an experimental research with 36 research samples. The samples were attached on an acrylic board and soaked with different temperatures. The force was measured with force gauge NK-500 and noted within 0 hour, 24 hours, 72 hours, 168 hours and 240 hours. Result: The result of this research was statistically done by using Kruskal Wallis (α= 0,05). The temperature changes in each treatment that set based on different length of time showed that there was a reduction of force both in elastic chain and nickel titanium closed coil spring. In line with the research result, the reduction force in nickel titanium closed coil spring was higher than in elastic chain. Conclusion: Temperature changes can alter the force in nickel titanium closed coil spring and elastic chain.